Molecular Identification of Anopheles minimus sensu lato and Anopheles dirus sensu lato (Diptera: Culicidae) from Kampong Spoe Province, Cambodia - Ma, Yajun; Vanne, Sok; Li, Shizhu; Yang, Pin (Zootaxa, 2005)
Anopheles dirus and An. minimus are primary malaria vectors in Cambodia. Both are species complexes and can be confused on the basis of adult morphology. The second internal transcribed spacer (ITS2) and the third domain (D3) in 28S of ribosomal DNA (rDNA) of An. minimus sensu lato and An. dirus s. l. were sequenced and analyzed. Three species (An. minimus A, An. sawadwongporni, and An. pampanai) and three sequence variants (MYJ-1, MYJ-2 and MYJ-3) were identified in An. minimus s. l. Two species (An. dirus A, An. pampanai) and one sequence variant (MYJ-1) were identified in An. dirus s. l. Anopheles sawadwongporni is recorded for the first time in Cambodia.